the equation is made and the included values are indicated.
= 4.95 X .65 = 3.2175 ( 3.22).
4.95 = 100% of the price
100 less 35 = 65
4.95 X .65% = 3.2175 or 3.22
Answer:
b is the answer
Step-by-step explanation:
PrimeAnswer:
Step-by-step explanation:
QUESTION 1
We want to solve,
![\frac{1}{(x-4)}+\frac{x}{(x-2)}=\frac{2}{x^{2}-6x+8}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%28x-4%29%7D%2B%5Cfrac%7Bx%7D%7B%28x-2%29%7D%3D%5Cfrac%7B2%7D%7Bx%5E%7B2%7D-6x%2B8%7D)
We factor the denominator of the fraction on the right hand side to get,
![\frac{1}{(x-4)}+\frac{x}{(x-2)}=\frac{2}{x^{2}-4x - 2x+8}.](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%28x-4%29%7D%2B%5Cfrac%7Bx%7D%7B%28x-2%29%7D%3D%5Cfrac%7B2%7D%7Bx%5E%7B2%7D-4x%20-%202x%2B8%7D.)
This implies
![\frac{1}{(x-4)}+\frac{x}{(x-2)}=\frac{2}{x(x-4) - 2(x - 4)}.](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%28x-4%29%7D%2B%5Cfrac%7Bx%7D%7B%28x-2%29%7D%3D%5Cfrac%7B2%7D%7Bx%28x-4%29%20-%202%28x%20-%204%29%7D.)
![\frac{1}{(x-4)}+\frac{x}{(x-2)}=\frac{2}{(x-4)(x - 2)}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%28x-4%29%7D%2B%5Cfrac%7Bx%7D%7B%28x-2%29%7D%3D%5Cfrac%7B2%7D%7B%28x-4%29%28x%20-%202%29%7D)
We multiply through by LCM of
![(x-4)(x - 2)](https://tex.z-dn.net/?f=%28x-4%29%28x%20-%202%29)
![(x - 2) + x(x-4) = 2](https://tex.z-dn.net/?f=%28x%20-%202%29%20%2B%20x%28x-4%29%20%3D%202)
We expand to get,
![x - 2 + {x}^{2} - 4x= 2](https://tex.z-dn.net/?f=x%20-%202%20%2B%20%7Bx%7D%5E%7B2%7D%20-%204x%3D%202)
We group like terms and equate everything to zero,
![{x}^{2} + x - 4x - 2 - 2 = 0](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%2B%20x%20-%204x%20-%202%20-%202%20%3D%200)
We split the middle term,
![{x}^{2} + - 3x - 4 = 0](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%2B%20-%203x%20-%204%20%3D%200)
We factor to get,
![{x}^{2} + x - 4x- 4 = 0](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%2B%20x%20-%204x-%204%20%3D%200)
![x(x + 1) - 4(x + 1) = 0](https://tex.z-dn.net/?f=x%28x%20%2B%201%29%20-%204%28x%20%2B%201%29%20%3D%200)
![(x + 1)(x - 4) = 0](https://tex.z-dn.net/?f=%28x%20%2B%201%29%28x%20-%204%29%20%3D%200)
![x + 1 = 0 \: or \: x - 4 = 0](https://tex.z-dn.net/?f=x%20%2B%201%20%3D%200%20%5C%3A%20or%20%5C%3A%20x%20-%204%20%3D%200)
![x = - 1 \: or \: x = 4](https://tex.z-dn.net/?f=x%20%3D%20-%201%20%5C%3A%20or%20%5C%3A%20x%20%3D%204)
But
![x = 4](https://tex.z-dn.net/?f=x%20%3D%204)
is not in the domain of the given equation.
It is an extraneous solution.
![\therefore \: x = - 1](https://tex.z-dn.net/?f=%20%5Ctherefore%20%5C%3A%20x%20%3D%20-%201)
is the only solution.
QUESTION 2
![\sqrt{x+11} -x=-1](https://tex.z-dn.net/?f=%5Csqrt%7Bx%2B11%7D%20-x%3D-1)
We add x to both sides,
![\sqrt{x+11} =x-1](https://tex.z-dn.net/?f=%5Csqrt%7Bx%2B11%7D%20%3Dx-1)
We square both sides,
![x + 11 = (x - 1)^{2}](https://tex.z-dn.net/?f=x%20%2B%2011%20%3D%20%28x%20-%201%29%5E%7B2%7D%20)
We expand to get,
![x + 11 = {x}^{2} - 2x + 1](https://tex.z-dn.net/?f=x%20%2B%2011%20%3D%20%7Bx%7D%5E%7B2%7D%20-%202x%20%2B%201)
This implies,
![{x}^{2} - 3x - 10 = 0](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20-%203x%20-%2010%20%3D%200)
We solve this quadratic equation by factorization,
![{x}^{2} - 5x + 2x - 10 = 0](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20-%205x%20%2B%202x%20-%2010%20%3D%200)
![x(x - 5) + 2(x - 5) = 0](https://tex.z-dn.net/?f=x%28x%20-%205%29%20%2B%202%28x%20-%205%29%20%3D%200)
![(x + 2)(x - 5) = 0](https://tex.z-dn.net/?f=%28x%20%2B%202%29%28x%20-%205%29%20%3D%200)
![x + 2 = 0 \: or \: x - 5 = 0](https://tex.z-dn.net/?f=x%20%2B%202%20%3D%200%20%5C%3A%20or%20%5C%3A%20x%20-%205%20%3D%200)
![x = - 2 \: or \: x = 5](https://tex.z-dn.net/?f=x%20%3D%20-%202%20%5C%3A%20or%20%5C%3A%20x%20%3D%205)
But
![x = - 2](https://tex.z-dn.net/?f=x%20%3D%20-%202)
is an extraneous solution